The Political Significance of Overeducation: Status Inconsistency, Attitudes towards the Political System and Political Participation in a High-Overeducation Context - Carmen Voces; Miguel Caínzos (Social Sciences, 2022)
This article examines the impact of overeducation on attitudes towards the political system and political participation. Using survey data from Spain, diagonal reference models were estimated to contrast hypotheses based on the theory of status inconsistency. The evidence links overeducation to political attitudes (lower satisfaction with the functioning of democracy, lower external political efficacy) and political participation (greater participation in protests, higher membership in associations). Most of these effects are modest and some of them are moderated by age. Overall, the findings indicate that overeducation has relevant political consequences, mainly among young, university-educated workers doing jobs with low educational requirements. However, overeducation does not pose a major threat to political stability.